2021
DOI: 10.3390/metabo11050330
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Small Heterodimer Partner Mediates Sex-Specific Effects on Triglyceride Metabolism via Androgen Receptor in Male Mice

Abstract: Mechanisms of sex differences in hypertriglyceridemia remain poorly understood. Small heterodimer partner (SHP) is a nuclear receptor that regulates bile acid, glucose, and lipid metabolism. SHP also regulates transcriptional activity of sex hormone receptors and may mediate sex differences in triglyceride (TG) metabolism. Here, we test the hypothesis that hepatic SHP mediates sex differences in TG metabolism using hepatocyte-specific SHP knockout mice. Plasma TGs in wild-type males were higher than in wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
2
4
0
Order By: Relevance
“…In hepatic SHP knockout mice, the mRNA levels of hepatic lipid receptors (Srarb1 and Vldlr) and cholesterol transporters (Abcg5/8) were upregulated ( Figure 7 D). In line with this, the increased liver lipid uptake associated with the downregulation of hepatic SHP has been reported by different groups [ 9 , 16 , 20 ]. It has been reported that the bile acid pool size in the liver can be enlarged in SHP knockout mice due to the lack of suppression of Cyp7a1 and/or Cyp8b1 expression [ 9 , 13 , 20 , 46 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In hepatic SHP knockout mice, the mRNA levels of hepatic lipid receptors (Srarb1 and Vldlr) and cholesterol transporters (Abcg5/8) were upregulated ( Figure 7 D). In line with this, the increased liver lipid uptake associated with the downregulation of hepatic SHP has been reported by different groups [ 9 , 16 , 20 ]. It has been reported that the bile acid pool size in the liver can be enlarged in SHP knockout mice due to the lack of suppression of Cyp7a1 and/or Cyp8b1 expression [ 9 , 13 , 20 , 46 ].…”
Section: Discussionsupporting
confidence: 84%
“…SHP regulates sex hormonal signaling pathways by interacting with androgen receptors (AR) and estrogen receptors [ 7 , 8 ]. We previously demonstrated that liver SHP contributes to sex differences in blood TG levels in an AR-dependent manner [ 9 ]. SHP suppresses virus-mediated infection by repressing the transcription of type I interferon (IFN) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of importance, microsomal triglyceride transfer protein (MTP) plays a key role in the assembly of VLDL and CM via transporting the related lipids to apoB particles ( Iqbal et al, 2020 ). Furthermore, recent studies have demonstrated that CETP increases the production of VLDL-TG in response to estrogen treatment via enhancing the expression of nuclear receptor and small heterodimer partner in female CETP transgenic mice ( Palmisano et al, 2016 ; Palmisano et al, 2021 ). Therefore, some endogenous molecules, such as estrogen, mediate sex-specific modulation of TG metabolism.…”
Section: A Short Review Of Tg and Tgrlmentioning
confidence: 99%
“…98 Overall, it interacts with several other nuclear receptors, including the AR. 97,99 Shp acts as a mediating factor in the metabolic circadian clock. 100 It has been suggested that some atypical retinoids can act as ligands to promote its activity.…”
Section: Estrogen-related Receptorsmentioning
confidence: 99%
“…Moreover, Shp intercepts with the DNA binding of nuclear receptors 98 . Overall, it interacts with several other nuclear receptors, including the AR 97,99 . Shp acts as a mediating factor in the metabolic circadian clock 100 .…”
Section: Dax1 and Shpmentioning
confidence: 99%